2014
DOI: 10.1128/aem.01785-14
|View full text |Cite
|
Sign up to set email alerts
|

FLP-FRT-Based Method To Obtain Unmarked Deletions of CHU _ 3237 ( porU ) and Large Genomic Fragments of Cytophaga hutchinsonii

Abstract: Cytophaga hutchinsonii is a widely distributed cellulolytic bacterium in the phylum Bacteroidetes. It can digest crystalline cellulose rapidly without free cellulases or cellulosomes. The mechanism of its cellulose utilization remains a mystery. We developed an efficient method based on a linear DNA double-crossover and FLP-FRT recombination system to obtain unmarked deletions of both single genes and large genomic fragments in C. hutchinsonii. Unmarked deletion of CHU_3237 (porU), an ortholog of the C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…Inverse PCR showed that the transposon was inserted into gene locus chu_3220. To confirm this, chu_3220 was disrupted by linear DNA double-crossover deletion (27). The transformant was confirmed by PCR tests with primers 3220F/3220R and 3220F/3220E and named Δ3220.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Inverse PCR showed that the transposon was inserted into gene locus chu_3220. To confirm this, chu_3220 was disrupted by linear DNA double-crossover deletion (27). The transformant was confirmed by PCR tests with primers 3220F/3220R and 3220F/3220E and named Δ3220.…”
Section: Resultsmentioning
confidence: 99%
“…According to the potential start codon, the protein would contain 2,040 instead of 1,980 amino acids. To verify the actual start codon of chu_3220, we used the active promoter P 1284 that we had discovered previously (27) to replace the annotated and potential promoter of chu_3220 and obtained the Δ3220-A and Δ3220-P mutants, respectively (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations